Nicaragua - Poverty Assessment : Raising Welfare and Reducing Vulnerability - World Bank (Washington, DC, 2013)
This poverty assessment was launched with three broad objectives: (1) to update the poverty profile for Nicaragua with data from the 2001 LSMS survey and assess key changes between 1998 and 2001; (2) to review progress with respect to PRSP targets and Millennium Development Goals (MDGs), including an analysis of those areas where advances have been weak to orient greater public attention; and (3) analyze the dynamics o f families moving in and out o f poverty using panel data from the 1998 and 2001 LSMS surveys, in order to obtain clues about strategies that may have led to improving incomes. This report finds that Nicaragua has made significant progress in reducing poverty over the last decade, despite its status as one of the poorest and least developed countries in Latin America. Although poverty declined significantly more in rural than urban areas, poverty and extreme poverty continue to be overwhelmingly rural. Progress in poverty reduction between 1998 and 2001 reflect significant income gains for most Nicaraguan households as well as lower food prices. Better-off families in Nicaragua exhibit high educational levels, small family sizes, residence in Managua and the Pacific Region, and diversified incomes. However, poverty changes between 1998 and 2001 varied substantially by region. Despite overall gains in poverty, nearly half of all PRSP targets are not currently on track. The areas where indicators show least progress since 1993, raising concerns for prospects of future poverty reduction, include the following: 1). Fertility rates continue to be high in Nicaragua, particularly among adolescents with no education, and a large unsatisfied demand for family planning services continues. 2) Progress in education is mixed. 3) Productive infrastructure has been practically stagnant since the early 1990s. 4) Basic water and sanitation infrastructure has progressed very modestly, with less than half of the homes in rural areas having access to safe basic services. 5) Diarrhea and upper respiratory infections for children under five show little progress since the early 1990s. The report concludes that continued progress in Nicaragua's Millennium Development Goals and Poverty Reduction Strategy P goals will be closely linked to the recovery of growth. Successful strategies for broad-based growth and poverty reduction should include aiming for macroeconomic stability, key interventions in education, increased access to productive and basic infrastructure, increased competitiveness and efficiency in financial services would improve access to credit for poorer families, Increased access to reproductive and perinatal healthcare services for women with maternal and child care becoming a priority, and access to timely and targeted social protection interventions.